Faktor – Faktor Yang Mempengaruhi Kinerja Perusahaan Manufaktur - Jeremy, Viriany (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
This study was conducted to examine the effect of board of directors size, board gender, independent commissioner,institutional ownership, firm size, and debt ratio on firm performance in listed manufacturing companies in Indonesian Stock Exchange (IDX) period 2016-2018. The sample used in this study is 73 manufacturing companies. This study used fixed effect model and multiple regression analysis. The results of this study indicate that board of directors size, board gender, institutional ownership, and firm size have a insignificant effect on firm performance, independent commissioner and debt ratio have a significant positive effect on corporate firm performance.